The Role of Leader Communication in Increasing Employee Work Productivity at PT Bina Bestari, Semarang - Ahmad Fadzil*; Nyosisca Listyanti (Universitas Syiah Kuala, 2024)
The actions of a company constantly connect and bind the connection between different organizations via communication. If the firm does not have excellent communication, it can lead to conflict and impair employee productivity, which might hinder the establishment of the company's own objectives. For instance, at PT Bina Bestari Semaranga company that specializes in coordinating labor servicesa dispute develops when executives and workers fail to communicate, which in turn reduces staff productivity. This research will look at how PT. Bina Bestari's leadership has been able to boost staff performance and productivity via their communication strategies. This study employs a qualitative methodology based on a case study design, with data collected via in-depth interviews, participant observation, and written records. This study's findings suggest that leadership is doing a good job of carrying out their responsibilities and that the vertical communication model between superiors and subordinates may work as intended. All parties involved in the dispute at PT Bina Bestari division have acknowledged that things started to look better when it came to communication between workers and management, which in turn led to a rise in output